Penguatan Minat Studi Hukum Melalui Edukasi Pendidikan Tinggi dan Wirausaha (Sosialisasi Abdimas Generasi Muda Harus Berpendidikan dan Berjiwa Usaha di SMAN 2 Kota Tegal) - Kanti Rahayu; Kus Rizkianto; Mukhidin Mukhidin; Selviany Selviany (Jurnal Kabar Masyarakat, 2026)
The low level of academic motivation and the assumption that higher education does not always guarantee economic well-being have become major factors contributing to the declining interest of some senior high school students in pursuing higher education. This issue poses a serious challenge to human resource development, particularly in the field of legal studies. Such conditions are influenced by various factors, including limited understanding of the prospects and opportunities within legal education. The purpose of this community service activity was to provide information and understanding through repeated socialization programs aimed at strengthening students’ interest in legal studies through higher education combined with the development of entrepreneurial spirit among senior high school students. This program was intended to motivate students regarding career opportunities in the legal field as well as the integration of entrepreneurial skills within the professional legal sector. The results of the activities, which were conducted through lectures, discussions, and counseling methods, were successful in improving students’ understanding of the strategic role of legal studies in society, accompanied by insights into business and profession opportunities based on legal knowledge. Consequently, the program succeeded in increasing students’ motivation to continue their education at the university level. The entrepreneurial approach also fostered independent, creative, and adaptive mindsets toward the development of the modern labor market. Therefore, strengthening interest in legal studies through higher education and entrepreneurship education represents a strategic step in creating a competitive, ethical, and future-oriented younger generation